2013
DOI: 10.1089/ars.2011.4457
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Sensitive Oxidation and Phosphorylation of PTEN Contribute to Enhanced Activation of PI3K/Akt Signaling in Rostral Ventrolateral Medulla and Neurogenic Hypertension in Spontaneously Hypertensive Rats

Abstract: Aims: The activity of phosphoinositide 3-kinase (PI3K)/serine/threonine protein kinase (Akt) is enhanced under hypertension. The phosphatase and tensin homolog deleted on chromosome 10 (PTEN) is a negative regulator of PI3K signaling, and its activity is redox-sensitive. In the rostral ventrolateral medulla (RVLM), which is responsible for the maintenance of blood pressure, oxidative stress plays a pivotal role in neurogenic hypertension. The present study evaluated the hypothesis that redox-sensitive inactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 59 publications
(84 reference statements)
3
31
0
Order By: Relevance
“…It is reported that the activity of the PI3K/AKT pathway is enhanced in the RVLM of SHR, and the phosphorylation of AKT in the PVN of hypertensive rats is also increased . Recently, we also confirmed that an inactivation of PI3K signaling in the RVLM is involved in antioxidative stress induced by central antihypertensive mechanism .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It is reported that the activity of the PI3K/AKT pathway is enhanced in the RVLM of SHR, and the phosphorylation of AKT in the PVN of hypertensive rats is also increased . Recently, we also confirmed that an inactivation of PI3K signaling in the RVLM is involved in antioxidative stress induced by central antihypertensive mechanism .…”
Section: Discussionsupporting
confidence: 78%
“…Previous evidence suggests that the phosphoinositide‐3 kinase (PI3K) pathway in the RVLM is involved in regulating BP and sympathetic outflow . It has been demonstrated that the PI3K signaling in the RVLM is upregulated in hypertension, and its inactivation leads to reduction in reactive oxygen species (ROS) production and cardiovascular function . Moreover, we recently report that gene knockdown of the PI3K subunit p110δ in the RVLM exerts the centrally antihypertensive action …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, overexpression of antioxidant enzymes such as SOD and catalase have been associated with production of H 2 O 2 and activated Akt signaling mediated by oxidized Pten [72]. The redox-sensitive interplay between Pten and Pi3k signaling is also involved in the pathogenesis of conditions such as hypertension [73]. Age-dependent down regulation of Pi3k signaling is associated with increased susceptibility to oxidative stress [74].…”
Section: Discussionmentioning
confidence: 99%
“…In myocardium, Akt kinase has been considered as a reperfusion injury salvage kinase, counteracting oxidative stress-induced cell damage through a compensatory protective pathway [65]. In the RVLM of brain stem, ROS activates PI3K/Akt signaling via oxidation and phosphorylation of the phosphatase and tensin homolog deleted on chromosome 10, which is a negative regulator of PI3K signaling [66]. This redox-sensitive overactivation of PI3K/Akt signaling contributes to neural mechanisms of hypertension in SHR.…”
Section: Reviewmentioning
confidence: 99%